PEMANFAATAN DIGITAL MARKETING SEBAGAI MEDIA PROMOSI UNTUK MENINGKAT VOLUME PENJUALAN PADA USAHA TOKO ROTI SARI GOOD CIMAHI - Ade Ratnawati; Sudrartono, Tiris (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This study aims to determine the problems that occur in the sales system used by Sari Good Bakery which has an impact on decreasing sales volume, efforts that can be made to overcomethe problems of the sales system are carried out through promotions using digital marketing on Instagram social media. This study uses a qualitative descriptive method of data from interviews and observations to provide a more in-depth description and information and describe how to increase sales volume for Sari Good bakery after utilizing digital marketing asa promotional medium. Sales features such as Instagram ads, stories, and also hashtags in overcoming the decline in December then after using Instagram as a promotional medium in January, the reach of Instagram customers increased quite a bit, as seen from the increase infollowers, besides that it had an impact on increasing sales volume from December sales of 15,057 pcs. Bread increased to 17,351 up to 15% in January. The latest info such as discounts,and new products at the Sari Good Bakery store. In addition to the use of digital marketing byusing other media to expand the target market, such as other social media and marketplaces.